α 1-Antitrypsin and serum albumin mRNA accumulation in normal, acute phase and ZZ human liver - Riley, J.H.; Bathurst, I.C.; Edbrooke, M.R.; Carrell, R.W.; Craig, R.K. (FEBS letters, 1985)
α 1-Antitrypsin and albumin mRNA levels of 4 human livers were assessed using a newly sequenced cDNA clone of the carboxyterminal third of α 1-antitrypsin and a previously cloned albumin cDNA sequence. The relative concentration of α 1-antitrypsin mRNA was the same in poly(A)-containing RNA isolated from acute phase (MM) and α 1-antitrypsin deficient (ZZ) individuals. In the acute phase liver relative to the normal (MM) liver, total RNA extracts showed a marked decrease in albumin mRNA concentration but no increase in α 1-antitrypsin mRNA. The ZZ liver showed decreased total and poly(A)-containing RNA content but the same proportion of α-antitrypsin to albumin mRNA as in the normal (MM) liver. This supports other evidence that ZZ α 1-antitrypsin deficiency is due to a defect in polypeptide processing (secretion) rather than a deficiency in mRNA accumulation.